Changes in physiological and endurance parameters in elite women water polo players during preparatory period - Radovanovic, D.; Aleksandrovic, M.; Okicic, T.; Ignjatovic, A. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The preparatory period in water polo is a complex combination of different types of training (strength, endurance and speed training) and the tactical practice of attack and defense movements (individual, group and collective). The most important competitions (Olympic Games, World and European Championships) are played by the tournament system which demands top level of physical readiness of players while avoiding the risk of overtraining syndrome. In the present study, the changes in physiological and endurance parameters were monitored at the beginning and at the end of the 14 weeks continuous preparatory period before the 2006 European championship. Endurance trainings were repeated periodically during the course of a certain mesocycle in combination with situational tactical trainings. Twelve water polo players (age: 23.8 years ± 3.1, height: 173.2cm ± 3.9, body weight: 65.7kg ± 6.7, body fat 18.3% ± 4.9) of the Serbian women`s national water polo team completed pre and post preparatory test protocol. Laboratory tests were used for assessing muscle power of upper limb (mean power-MP), upper body oxygen uptake (VO2peak) and forced expiratory in 1 second (FEV1). Endurance was assessed by two tests: one by 2000 m (5x400m) free style swims and the second by 2400 m (12x200m) free style swims (in a 50 m pool). Anaerobic capacity was assessed by maximal test of 10 all out 50 m free style swims. Results show that there were no significant changes in mean power (426.24W±70.6 pre vs. 430.56W±58.8 post) and FEV1 (4.6L±0.6 pre vs. 4.6L±0.4 post). VO2peak was significantly higher after preparatory period (42.2ml.kg-1.min-1±3.9 pre vs. 46.52ml.kg-1.min-1±7.0 post). Mean time achieved during test on 400m free style swims was significantly shorter (346s±6.7 pre vs. 331s±5.2 post). Mean time achieved during test on 200m free style swims was significantly shorter (158s±4.7 pre vs. 145s±3.9 post). Mean time achieved during maximal test of ten all out 50 m free style swims was shorter by 1.99%±1.5 (36.2s±1.5 pre vs. 35.5s±1.8 post). No correlation was found between the mean power value achieved on the arm ergometer and the time at the maximal anaerobic test of ten all out 50 m free style swims. Our study provides a quantitative representation of physiological and endurance parameters in female water polo players, and proposes a useful battery of tests that can be used for assessing the status of players.